WACANA KRITIS SARA MILLS DALAM KASUS KDRT LESTI KEJORA PADA AKUN INSTAGRAM @LAMBETURAH_OFFICIAL - Wenerlee, Valend Young; Lin, Mila Kristina; Wahyuni, Ian (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
The purpose of this study is to describe the position of the subject and the position of the reader in the post on the @lambeturah_official Instagram account. This study uses a critical discourse analysis approach to media texts. To answer the research problem, the feminist theory initiated by Sara Mills is used. This research method uses qualitative methods and descriptive approaches. This type of research is literature, namely research where data is taken mainly from the literature (books, documents, articles, reports, newspapers, and so on). The data in this study are in the form of words, phrases, and sentences on Instagram social media that discuss the cases of domestic violence against Lesti and Rizky Billar. The data source in this study is the Instagram account @lambeturah_official which reports on the Lesti Kejora domestic violence case. The results of the study used Sara Mills' critical discourse analysis on the Instagram account @lambeturah_official showing Lesti Kejora as a woman's position (subject) and also from the reader's point of view raises concern for Lesti as a victim of domestic violence.